Raynaud's syndrome in children: systematic review and development of recommendations for assessment and monitoring - Pain, Clare E; Constantin, Tamás; Toplak, Natasa; Moll, Monica; Iking-Konert, Christof; Piotto, Daniella P; Aktay Ayaz, Nuray; Nemcova, Dana; Hoeger, Peter H; Cutolo, Maurizio; Smith, Vanessa; Foeldvari, Ivan (Clinical and Experimental Rheumatology, 2016)
OBJECTIVES: To develop recommendations for investigation and monitoring of children with Raynaud's syndrome, based on paediatric evidence collated by a systematic review. METHODS: A systematic review was undertaken to establish the paediatric evidence for assessment and monitoring of Raynaud's syndrome. An expert panel including members of the Paediatric Rheumatology European Society (PRES) Scleroderma Working Group, were invited to a consensus meeting where recommendations were developed based on evidence graded by the systematic review and where evidence was lacking, consensus opinion. A nominal technique was used where 75% consensus was taken as agreement. RESULTS: The expert panel recommended testing anti-nuclear antibody (ANA), more specific antibodies associated with connective tissue disease and nail-fold capillaroscopy in all children presenting with Raynaud's syndrome as data suggests these can be risk factors for evolution into a connective tissue disease. The frequency of follow-up recommended depends on presence of these risk factors with the aim to detect evolving connective tissue disease early in high risk individuals. Those with no abnormalities on capillaroscopy and negative autoantibodies were deemed low risk of progression, whereas those with ANA positivity, specific autoantibodies and/or nailfold capillary changes were deemed high risk and more frequent follow-up was recommended. CONCLUSIONS: Recommendations, primarily based on consensus opinion, were agreed regarding investigation and monitoring of children who present with Raynaud's syndrome. Further prospective studies are needed to better define the risk factors for progression to connective tissue disease.
Keywords: Raynaud Disease; Antibodies, Antinuclear; Female; Raynaudova nemoc; dítě; biologické markery; pediatrie; Age Factors; Biomarkers; ženské pohlaví; Predictive Value of Tests; Adolescent; prediktivní hodnota testů; věkové faktory; lidé; revmatologie; konsensus; Microscopic Angioscopy; mikroskopická angioskopie; prognóza; Consensus; Risk Factors; Male; progrese nemoci; Rheumatology; sérologické testy; mladiství; Disease Progression; rizikové faktory; Prognosis; Child; Serologic Tests; Pediatrics; mužské pohlaví; antinukleární protilátky; Humans